Practical guide to sample size calculations: an introduction. (20th November 2015) - Flight, Laura; Julious, Steven A.
Abstract : A sample size justification is a vital step when designing any trial. However, estimating the number of participants required to give a meaningful result is not always straightforward. A number of components are required to facilitate a suitable sample size calculation. In this paper, the general steps are summarised for conducting sample size calculations with practical advice and guidance on how to utilise the app SampSize. Copyright © 2015 John Wiley & Sons, Ltd.